Dual species sphingosine-1-phosphate lyase inhibitors to combine antifungal and anti-inflammatory activities in cystic fibrosis: a feasibility study - Barbara Cellini; Gioena Pampalone; Emidio Camaioni; Marilena Pariano; Flavia Catalano; Teresa Zelante; Mirco Dindo; Lara Macchioni; Alessandra Di Veroli; Roberta Galarini; Fabiola Paoletti; Magdalena Davidescu; et al. (Scientific Reports, 2023)
Abstract Cystic fibrosis (CF) is an autosomal recessive disorder characterized by respiratory failure due to a vicious cycle of defective Cystic Fibrosis Transmembrane conductance Regulator (CFTR) function, chronic inflammation and recurrent bacterial and fungal infections. Although the recent introduction of CFTR correctors/potentiators has revolutionized the clinical management of CF patients, resurgence of inflammation and persistence of pathogens still posit a major concern and should be targeted contextually. On the background of a network-based selectivity that allows to target the same enzyme in the host and microbes with different outcomes, we focused on sphingosine-1-phosphate (S1P) lyase (SPL) of the sphingolipid metabolism as a potential candidate to uniquely induce anti-inflammatory and antifungal activities in CF. As a feasibility study, herein we show that interfering with S1P metabolism improved the immune response in a murine model of CF with aspergillosis while preventing germination of Aspergillus fumigatus conidia. In addition, in an early drug discovery process, we purified human and A. fumigatus SPL, characterized their biochemical and structural properties, and performed an in silico screening to identify potential dual species SPL inhibitors. We identified two hits behaving as competitive inhibitors of pathogen and host SPL, thus paving the way for hit-to-lead and translational studies for the development of drug candidates capable of restraining fungal growth and increasing antifungal resistance.